Mining low-bleeding self-strengthening solid waste filling material, preparation method and application

By using the synergistic effect of solid waste materials and additives such as weathered coal gangue, cement, fly ash, slag powder and other solid waste materials and additives, a low-secretion water self-reinforced solid waste filling material for minerals with stable structure, high water contact rate, and good anti-sinking performance, it solved the problems of poor stability and high water sealing rate of existing filling slurry, achieved efficient and economical filling effect, and promoted the green and low-carbon development in the mining field.

CN119504213APending Publication Date: 2025-02-25XIAN RES INST OF CHINA COAL TECH & ENG GRP CORP

Patent Information

Application Number
CN202411497025.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-25
Patent Text Reader

Abstract

The invention provides a mining low-bleeding self-reinforced solid waste filling material as well as a preparation method and application thereof. The mining low-bleeding self-reinforced solid waste filling material is prepared from the following raw material components: 340 to 480 parts of weathered coal gangue, 20 to 25 parts of cement, 30 to 40 parts of fly ash, 30 to 40 parts of slag powder, 0.3 to 0.7 part of sodium silicate, 5 to 7 parts of quick lime, 3 to 5 parts of magnesium oxide, 0.05 to 0.1 part of water-absorbent resin, 0.2 to 0.4 part of fiber and 160 to 245 parts of water. The slump of the filling material is 24-27 cm, the bleeding rate is smaller than 1%, the compressive strength of the filling material in 3 days is 1-2 MPa, the compressive strength of the filling material in 28 days is 3-6 MPa, and the drying shrinkage is-20-0 mm / m. The main solid raw materials used in the method are solid wastes, the purposes of stable filling material structure, low bleeding rate, self-strengthening in the curing process and the like are achieved by utilizing the characteristic and function synergy of various solid wastes, the mine filling production cost can be effectively saved, the resource treatment of bulk solid wastes in the mining industry field is realized, and the economic benefit is increased. Geological disaster and environmental pollution risks of mining areas are reduced, ecological management cost is reduced, economic benefits are created for mines, and meanwhile green and low-carbon development of the mining industry is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of mine filling and mining, and in particular relates to a low-seepage self-reinforced solid waste filling material for mining, a preparation method and an application thereof. Background Art

[0002] The process of coal mining generates a large number of underground goafs, which can easily lead to geological disasters such as surface cracks and collapses, and also generate a large amount of waste such as coal gangue. According to statistics, the stockpile of coal gangue in my country has exceeded 7 billion tons, and in the natural environment, coal gangue is prone to weathering and disintegration. Long-term storage can have an adverse impact on the environment.

[0003] With the continuous improvement of mine safety and environmental protection requirements, the application of cementing filling technology, which can effectively reduce geological disasters caused by coal mining and protect the ecological environment, has become more and more extensive in the field of coal mining. In coal mine cementing filling, coal gangue is often used as aggregate, cement is used as cementing material, and water is mixed to prepare filling slurry. Weathered coal gangue is easy to crush and consumes less energy, but its particle grading after crushing is defective, and slurry segregation is prone to occur. In addition, the cement consumption is large, the water seepage rate is high, and the filling body has poor anti-sinking performance, which affects underground production efficiency and low-carbon development of mines. At present, relevant work has been carried out in the field of filling mining on the utilization of solid waste materials such as coal gangue, fly ash, and slag, but there are still deficiencies in the multi-functional synergy of filling slurry such as low water seepage, self-strengthening, and anti-sinking. Therefore, how to make full use of bulk solid waste materials such as weathered coal gangue, fly ash, and slag to achieve multi-component synergy and prepare filling slurry with strong structural stability, good filling effect, and anti-sinking performance is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low-water seepage self-reinforcing solid waste filling material for mining, a preparation method and an application. This low-water seepage self-reinforcing solid waste filling material for mining uses solid waste as the main raw material and utilizes the synergistic effect between different material components. It has the advantages of stable slurry structure, low water seepage rate, high top connection rate and good anti-shrinkage performance, and is suitable for underground filling in mines.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0006] A low-seepage self-reinforcing solid waste filling material for mining includes the following raw material components by weight: 340-480 parts of weathered coal gangue, 20-25 parts of cement, 30-40 parts of fly ash, 30-40 parts of slag powder, 0.3-0.7 parts of sodium silicate, 5-7 parts of quicklime, 3-5 parts of magnesium oxide, 0.05-0.1 parts of water-absorbing resin, 0.2-0.4 parts of fiber and 160-245 parts of water.

[0007] The present invention also has the following technical features:

[0008] Specifically, the weathered coal gangue has a SiO2 content of 55-60wt%, an Al2O3 content of 20-25wt%, a Fe2O3 content of 5-9wt%, and a SO3 content of 3-6wt%.

[0009] Furthermore, the SiO2 content in the fly ash is 40-45wt%, and the Al2O3 content is 36-42wt%; the CaO content in the slag powder is 38.0-42.0wt%, the SiO2 content is 27.0-32.0wt%, the Al2O3 content is 15.0-18.0wt%, and the MgO content is 5.0-10wt%; the CaO content in the quicklime is greater than 90.0wt%.

[0010] Furthermore, the water-absorbing resin is selected from one or more of polyacrylic acid-based high molecular water-absorbing resins, cellulose-based high water-absorbing resins and polyacrylamide-based high water-absorbing resins.

[0011] Furthermore, the fiber is selected from one of polypropylene fiber and basalt fiber, and the fiber has a diameter of 15 to 35 μm and a length of 6 to 20 mm.

[0012] Furthermore, the particle size of the weathered coal gangue is ≤20 mm; and the particle size of the water-absorbing resin is 10-20 μm.

[0013] Furthermore, the slump of the low-bleeding self-reinforcing solid waste filling material for mining is 24-27 cm, the water seepage rate is less than 1%, the 3-day compressive strength is 1-2 MPa, the 28-day compressive strength is 3-6 MPa, and the drying shrinkage is -20-0 mm / m.

[0014] The present invention also protects a method for preparing a low-bleeding self-reinforced solid waste filling material for mining, comprising the following steps:

[0015] Step 1, screening the weathered coal gangue, using the weathered coal gangue with a particle size greater than 150 μm as coal gangue aggregate, and using the weathered coal gangue with a particle size less than 150 μm as coal gangue powder;

[0016] Step 2, activating the coal gangue powder to obtain activated coal gangue powder;

[0017] Step 3: Take the formulated amount of coal gangue aggregate, activated coal gangue powder, fly ash and slag powder and mix them evenly to obtain filling dry material A;

[0018] Step 4, taking the formulated amount of cement, quicklime, water-absorbing resin, magnesium oxide and fiber, mixing and stirring evenly to obtain filling dry material B;

[0019] Step 5, mixing the formulated amount of sodium silicate and water to obtain a sodium silicate aqueous solution;

[0020] Step 6, mixing the filling dry material A, the filling dry material B and the sodium silicate aqueous solution to obtain;

[0021] Among them, the low-seepage self-reinforcing solid waste filling material for mining includes the following raw material components in parts by weight: 340-480 parts of weathered coal gangue, 20-25 parts of cement, 30-40 parts of fly ash, 30-40 parts of slag powder, 0.3-0.7 parts of sodium silicate, 5-7 parts of quicklime, 3-5 parts of magnesium oxide, 0.05-0.1 parts of water-absorbing resin, 0.2-0.4 parts of fiber and 160-245 parts of water.

[0022] The present invention also protects the use of the above-mentioned low-water seepage self-reinforcing solid waste filling material for mining for filling and mining; or the use of the low-water seepage self-reinforcing solid waste filling material for mining obtained by the preparation method of the above-mentioned low-water seepage self-reinforcing solid waste filling material for mining for filling and mining.

[0023] Compared with the prior art, the present invention has the following technical effects:

[0024] (1) The filling material provided by the present invention has the advantages of stable structure and low water bleeding rate. The water-absorbing resin is used as a regulator to effectively reduce the free water distribution between particles in the slurry in the initial mixing stage and reduce the water bleeding of the slurry. As the hydration reaction proceeds, the water-absorbing resin can gradually release water for the later hydration of the cementitious material inside the filling body, thereby realizing self-control of the water content of the filling material system. By adding fibers to establish a matrix skeleton inside the filling slurry, a network is formed inside the filling body in combination with the hydration of the cementitious material to block the propagation of cracks after the filling body is damaged.

[0025] (2) The main solid raw materials used in the preparation method of the present invention are all solid waste materials. The characteristics of various solid wastes and the functional synergy based on multi-component additives are utilized to achieve the goals of stable filling material structure, low water seepage rate, and self-strengthening of the solidification process. This can effectively save the production cost of mine filling, realize the resource disposal of large amounts of solid waste in the mining field, reduce the risks of geological disasters and environmental pollution in mining areas, reduce the cost of ecological governance, create economic benefits for mines, and also promote the green and low-carbon development of the mining industry. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by any ordinary technician in the field belong to the scope of protection of the present invention.

[0027] It should be noted that all raw materials in the present invention, unless otherwise specified, are raw materials known in the art.

[0028] The technical concept of this application is: weathered coal gangue, fly ash and slag are all large solid wastes in the mining industry, and all have potential cementing activity. Each substance can play a complementary role in particle grading and chemical composition, and can form cementing properties under the action of additives. Based on the difference in the intensity of the reaction between sodium silicate, quicklime and magnesium oxide and water and the strength of alkalinity; sodium silicate and quicklime are used to quickly stimulate the dissolution of the vitreous in fly ash and slag to release active components, specifically including: after the slurry is mixed, the cement directly undergoes a hydration reaction, and cementing substances such as CSH and CH are generated under the promotion of sodium silicate, quicklime, etc., and the cement hydration cooperates with the dissolution of sodium silicate, quicklime and magnesium oxide to release OH - , forming an alkaline environment and releasing H2SiO4 2- 、SiO3 2- , Ca 2+ Mg 2 etc., OH - It promotes the dispersion and dissolution of the glass in slag and fly ash, releases active ingredients such as calcium, silicon, and aluminum, and generates Ca 2+ 、H2SiO4 2- 、H2AlO3 - Then the active substances in the system react to generate CSH, CAH, CASH, MSH gel, as well as CH, brucite, zeolite minerals, etc., which further enhance the strength of the filling body. The reaction process of this filling material system has a step-by-step synergistic effect: after the slurry is mixed, since the reaction intensity of sodium silicate and calcium oxide with water is higher than that of magnesium oxide, and the solubility of Ca(OH)2 in water is significantly greater than that of Ma(OH)2, in the initial stage of mixing, sodium silicate and calcium oxide mainly provide OH to maintain the alkaline environment. - , promoting the dissolution of active substances in slag, fly ash and coal gangue, and reacting with silicon and aluminum minerals to form CSH, CASH, etc. At this stage, the hydration of magnesium oxide is limited, thereby avoiding early expansion damage; as time goes on, the filling body forms a certain strength, and sodium silicate and calcium oxide are gradually hydrated and consumed, their contribution to maintaining the alkaline environment decreases, the output of gel substances such as CSH decreases, and the competition of Ca(OH)2 is weakened, which enhances the hydration reaction of magnesium oxide and the process of generating Ma(OH)2 (brucite). The growth and development of brucite crystals produce a micro-expansion effect, filling the micro-pore space inside the filling material, preventing and reducing the shrinkage of the filling material after solidification, and Ma(OH)2 and H2SiO4 released in the system 2- Further reaction generates MSH gel, which fills the internal micropores of the filling material and continues to strengthen the filling body, thereby achieving self-healing and self-strengthening of potential damage to the filling body under downhole stress.

[0029] In summary, the present invention achieves synergistic enhancement among different solid waste materials through component complementarity and gradient stimulation of various substances, and solves the technical problems of poor slurry stability, high water seepage rate, poor top connection effect, high filling cost and large carbon emissions in the existing cement bonding filling system.

[0030] In this application, the requirements for the various materials used are as follows:

[0031] Weathered coal gangue is weathered coal gangue accumulated on the ground, which is processed by crushing, grinding and screening, and the particle size of the coal gangue powder after grinding mainly includes less than 20mm. Among them, weathered coal gangue with a particle size greater than 150μm is mainly used as aggregate.

[0032] The SiO2 content in weathered coal gangue is 55-60wt%, the Al2O3 content is 20-25wt%, the Fe2O3 content is 5-9wt%, and the SO3 content is 3-6wt%.

[0033] The SiO2 content in fly ash is 40-45wt%, and the Al2O3 content is 36-42wt%;

[0034] The slag powder has a CaO content of 38.0-42.0wt%, a SiO2 content of 27.0-32.0wt%, an Al2O3 content of 15.0-18.0wt%, and a MgO content of 5.0-10wt%;

[0035] The CaO content in quicklime is greater than 90.0wt%.

[0036] The cement is ordinary Portland cement with a strength grade of 42.5R.

[0037] Sodium silicate is a solid sodium silicate powder with a modulus of 1.0 to 3.0.

[0038] The magnesium oxide is industrial grade lightly burned magnesium oxide powder, wherein the MgO content is greater than 85%.

[0039] The water-absorbing resin is selected from one or more of polyacrylic acid-based high molecular water-absorbing resin, cellulose-based high water-absorbing resin and polyacrylamide-based high water-absorbing resin, and the particle size of the water-absorbing resin is 10-20 μm.

[0040] The fiber is selected from one of polypropylene fiber and basalt fiber, and the fiber has a diameter of 15 to 35 μm and a length of 6 to 20 mm.

[0041] The invention provides a low-bleeding self-reinforcing solid waste filling material for mining, which comprises the following raw material components in parts by weight: 340-480 parts of weathered coal gangue, 20-25 parts of cement, 30-40 parts of fly ash, 30-40 parts of slag powder, 0.3-0.7 parts of sodium silicate, 5-7 parts of quicklime, 3-5 parts of magnesium oxide, 0.05-0.1 parts of water-absorbing resin, 0.2-0.4 parts of fiber and 160-245 parts of water.

[0042] Furthermore, the slump of the low-bleeding self-reinforcing solid waste filling material for mining is 24 to 27 cm, the water seepage rate is less than 1%, the 3-day compressive strength is 1 to 2 MPa, the 28-day compressive strength is 3 to 6 MPa, and the drying shrinkage is -20 to 0 mm / m.

[0043] The present invention also discloses a method for preparing a low-bleeding self-reinforced solid waste filling material for mining, comprising the following steps:

[0044] Step 1, screening the weathered coal gangue, using the weathered coal gangue with a particle size greater than 150 μm as coal gangue aggregate, and using the weathered coal gangue with a particle size less than 150 μm as coal gangue powder;

[0045] Step 2, activating the coal gangue powder to obtain activated coal gangue powder;

[0046] Step 3: Take the formulated amount of coal gangue aggregate, activated coal gangue powder, fly ash and slag powder and mix them evenly to obtain filling dry material A;

[0047] Step 4, taking the formulated amount of cement, quicklime, water-absorbing resin, magnesium oxide and fiber, mixing and stirring evenly to obtain filling dry material B;

[0048] Step 5, mixing the formulated amount of sodium silicate and water to obtain a sodium silicate aqueous solution;

[0049] Step 6: Mix the filling dry material A, the filling dry material B and the sodium silicate aqueous solution to obtain.

[0050] The present invention also discloses the use of the above-mentioned low-water seepage self-reinforcing solid waste filling material for mining in filling and mining; or the use of the low-water seepage self-reinforcing solid waste filling material for mining prepared by the preparation method of the above-mentioned low-water seepage self-reinforcing solid waste filling material for mining in filling and mining.

[0051] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0052] Example 1

[0053] The raw materials used in this embodiment are as follows: weathered coal gangue is taken from the gangue pile of a coal mine in northern Shaanxi, and the main particle size is: D10 =74μm, D 60 =560μm, the curvature coefficient and the unevenness coefficient are 0.62 and 7.57 respectively; the weathered coal gangue contains 56.8wt% SiO2, 23.3wt% Al2O3, 7.94wt% Fe2O3, and 4.27wt% SO3.

[0054] Fly ash particle size: D 10 =3.955μm, D 50 =23.11μm, D 90 =110.3μm, and the SiO2 content in the fly ash is 44.04wt%; the Al2O3 content is 40.75wt%.

[0055] Slag powder particle size: D 10 =0.897μm, D 50 =11.06μm, D 90 =28.84μm, and the CaO content in the slag powder is 40.3wt%; the SiO2 content is 29.6wt%; the Al2O3 content is 16.3wt%; and the MgO content is 8.2wt%.

[0056] The CaO content in quicklime is 91.1wt%.

[0057] The water-absorbing resin is a polyacrylic acid-based high-molecular water-absorbing resin with a particle size of 10 to 20 μm.

[0058] The magnesium oxide is industrial magnesium oxide powder, and the content of MgO is 88%.

[0059] The fiber is polypropylene fiber with a diameter of 31μm and a length of 12mm.

[0060] In accordance with the above technical solution, this embodiment discloses a method for preparing a low-bleeding self-reinforced solid waste filling material for mining, comprising the following steps:

[0061] Step 1, screening the weathered coal gangue, using the weathered coal gangue with a particle size greater than 150 μm as coal gangue aggregate, and using the weathered coal gangue with a particle size less than 150 μm as coal gangue powder;

[0062] Step 2, activating the coal gangue powder to obtain activated coal gangue powder;

[0063] Step 3: Take the formulated amount of coal gangue aggregate, activated coal gangue powder, fly ash and slag powder and mix them evenly to obtain filling dry material A;

[0064] Step 4, taking the formulated amount of cement, quicklime, water-absorbing resin, magnesium oxide and fiber, mixing and stirring evenly to obtain filling dry material B;

[0065] Step 5, mixing the formulated amount of sodium silicate and water to obtain a sodium silicate aqueous solution;

[0066] Step 6: Mix the filling dry material A, the filling dry material B and the sodium silicate aqueous solution to obtain.

[0067] Among them, the low-seepage self-reinforcing solid waste filling material for mining includes the following raw material components by weight: 402 parts of weathered coal gangue, 25 parts of cement, 30 parts of fly ash, 40 parts of slag powder, 0.5 parts of sodium silicate, 5 parts of quicklime, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 197 parts of water.

[0068] The mixed slurry was injected into a triple test mold with a single cavity size of 70.7mm×70.7mm×70.7mm, and the curing and performance tests were carried out according to the curing and measurement methods in the "Standard Test Method for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016), "Standard Test Method for Physical and Mechanical Properties of Concrete" (GB / T50081-2019), and "Test Method for Coal Mine Paste Filling Materials" (NB / T 51070-2017).

[0069] During the slurry preparation process, a portion of the mixed slurry is taken for testing of slump and water seepage rate.

[0070] After testing, the slump of the low-bleeding self-reinforcing solid waste filling material for mining prepared in this embodiment is 25.6 cm, the water bleeding rate is 0.13%, the 3d compressive strength is 1.74 MPa, the 7d compressive strength is 2.53 MPa, the 28d compressive strength is 5.03 MPa, and the drying shrinkage is -14 mm / m.

[0071] The low water seepage self-strengthening solid waste filling material for mining provided in this embodiment can be used for filling and mining in mining areas.

[0072] Example 2

[0073] The low-exudation self-reinforcing solid waste filling material for mining disclosed in this embodiment has the same raw material components and preparation method as those disclosed in Example 1, with the only difference being the different ratios of the raw material components. The raw material components of this embodiment are: 410 parts of weathered coal gangue, 25 parts of cement, 40 parts of fly ash, 30 parts of slag powder, 0.7 parts of sodium silicate, 5 parts of quicklime, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 196 parts of water.

[0074] After testing, the slump of the low-bleeding self-reinforcing solid waste filling material for mining prepared in this embodiment is 24.8 cm, the water bleeding rate is 0.15%, the 3d compressive strength is 1.83 MPa, the 7d compressive strength is 2.61 MPa, the 28d compressive strength is 4.84 MPa, and the drying shrinkage is -15 mm / m.

[0075] Example 3

[0076] The low-exudation self-reinforcing solid waste filling material for mining disclosed in this embodiment has the same raw material components and preparation method as those disclosed in Example 1, with the only difference being the different proportions of the raw material components. The raw material components of this embodiment are: 342 parts of weathered coal gangue, 20 parts of cement, 30 parts of fly ash, 30 parts of slag powder, 0.5 parts of sodium silicate, 5 parts of quicklime, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 168 parts of water.

[0077] After testing, the slump of the low-bleeding self-reinforcing solid waste filling material for mining prepared in this embodiment is 25.1 cm, the water bleeding rate is 0.11%, the 3d compressive strength is 1.71 MPa, the 7d compressive strength is 2.48 MPa, the 28d compressive strength is 4.71 MPa, and the drying shrinkage is -12 mm / m.

[0078] Example 4

[0079] The low-exudation self-reinforcing solid waste filling material for mining disclosed in this embodiment has the same raw material components and preparation method as those disclosed in Example 1, with the only difference being the different ratios of the raw material components. The raw material components of this embodiment are: 430 parts of weathered coal gangue, 20 parts of cement, 40 parts of fly ash, 40 parts of slag powder, 0.7 parts of sodium silicate, 7 parts of quicklime, 4 parts of magnesium oxide, 0.07 parts of water-absorbing resin, 0.3 parts of polypropylene fiber and 212 parts of water.

[0080] After testing, the slump of the low-bleeding self-reinforcing solid waste filling material for mining prepared in this embodiment is 25.1 cm, the water bleeding rate is 0.11%, the 3d compressive strength is 1.71 MPa, the 7d compressive strength is 2.48 MPa, the 28d compressive strength is 4.71 MPa, and the drying shrinkage is -17 mm / m.

[0081] Comparative Example 1

[0082] This comparative example discloses a method for preparing solid waste filling material using cement and weathered coal gangue as raw materials. The raw material components include: 400 parts of weathered coal gangue, 100 parts of cement and 195 parts of water. The preparation method is: mix cement, weathered coal gangue and water, and stir evenly.

[0083] The prepared filling material was tested according to the method of Example 1.

[0084] After testing, the test results of the filling material prepared in this comparative example are: slump 24.1cm, water seepage rate 4.36%, 3d compressive strength 1.36MPa, 7d compressive strength 2.21MPa, 28d compressive strength 3.46MPa, drying shrinkage is 10mm / m.

[0085] Comparative Example 2

[0086] This comparative example provides a mining solid waste filling material, the properties of its raw material components and the preparation method are the same as the properties and preparation method of the raw material components disclosed in Example 1, the difference is that the raw material ratio is different and sodium silicate is not added in this comparative example. The raw material components of this comparative example include: 402 parts of weathered coal gangue, 25 parts of cement, 30 parts of fly ash, 40 parts of slag powder, 5 parts of quicklime, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 196 parts of water.

[0087] The prepared filling material was tested according to the method of Example 1.

[0088] After testing, the test results of the filling material prepared in this comparative example are: slump is 25.2cm, water seepage rate is 0.36%, 3d compressive strength is 0.74MPa, 7d compressive strength is 1.13MPa, 28d compressive strength is 1.86MPa, and drying shrinkage is -11mm / m.

[0089] Comparative Example 3

[0090] This comparative example provides a mining solid waste filling material, the properties of its raw material components and the preparation method are the same as the properties and preparation method of the raw material components disclosed in Example 1, the difference is that the raw material ratio is different and magnesium oxide is not added in this comparative example. The raw material components of this comparative example are: 382 parts of weathered coal gangue, 25 parts of cement, 30 parts of fly ash, 40 parts of slag powder, 0.5 parts of sodium silicate, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 187 parts of water.

[0091] The prepared filling material was tested according to the method of Example 1.

[0092] After testing, the test results of the filling material prepared in this comparative example are: slump is 25.7cm, water seepage rate is 1.02%, 3d compressive strength is 0.63MPa, 7d compressive strength is 1.26MPa, 28d compressive strength is 1.94MPa, and drying shrinkage is -10mm / m.

[0093] Comparative Example 4

[0094] This comparative example provides a mining solid waste filling material, the properties of its raw material components and the preparation method are the same as the properties and preparation method of the raw material components disclosed in Example 1, the difference is that the raw material ratio is different and no quicklime is added in this comparative example. The raw material components of this comparative example are: 402 parts of weathered coal gangue, 25 parts of cement, 30 parts of fly ash, 40 parts of slag powder, 0.5 parts of sodium silicate, 3 parts of magnesium oxide, 0.05 parts of water-absorbing resin, 0.2 parts of polypropylene fiber and 196 parts of water.

[0095] The prepared filling material was tested according to the method of Example 1.

[0096] After testing, the test results of the filling material prepared in this comparative example are: slump is 25.5cm, water seepage rate is 0.22%, 3d compressive strength is 1.42MPa, 7d compressive strength is 2.11MPa, 28d compressive strength is 4.12MPa, and drying shrinkage is -2mm / m.

[0097] Comparative Example 5

[0098] This comparative example provides a mining solid waste filling material, the properties of its raw material components and the preparation method are the same as the properties and preparation method of the raw material components disclosed in Example 1, the difference is that no water-absorbing resin is added in this comparative example, and the raw material components of this comparative example are: 402 parts of weathered coal gangue, 25 parts of cement, 30 parts of fly ash, 40 parts of slag powder, 0.5 parts of sodium silicate, 5 parts of quicklime, 3 parts of magnesium oxide, 0.2 parts of polypropylene fiber and 197 parts of water.

[0099] The prepared filling material was tested according to the method of Example 1.

[0100] After testing, the test results of the filling material prepared in this comparative example are: slump is 25.7cm, water seepage rate is 2.38%, 3d compressive strength is 1.65MPa, 7d compressive strength is 2.27MPa, 28d compressive strength is 4.29MPa, and drying shrinkage is -12mm / m.

[0101] It can be seen from Examples 1 to 4 that the low-bleeding self-strengthening high-doped solid waste filling material for mining has good fluidity and mechanical strength, and the water bleeding rate of the filling material is low, indicating that the slurry has good structural stability and good anti-segregation performance. When the fly ash / slag ratio is less than 1, the overall performance of the filling material is better, and when the fly ash and slag content increases, the content of sodium silicate and quicklime needs to be increased simultaneously to enhance the excitation effect; in addition, when the fly ash content is greater than the slag, the content of quicklime needs to be increased to a certain extent as a calcium source; in addition, the content of the water-absorbing resin needs to be adjusted accordingly with the content of other solid waste.

[0102] The performance of the filling materials obtained in Examples 1 to 4 is significantly better than that of the filling material prepared in Comparative Example 1.

[0103] From Example 1 and Comparative Examples 2 to 5, it can be seen that:

[0104] The sodium silicate, quicklime and magnesium oxide added in the present invention all have a positive effect on improving the performance of the filling material, especially, have a significant effect on the strength and water bleeding rate of the filling material, and the components have a synergistic effect. Among them, the addition of the water-absorbing resin can improve the water bleeding of the filling slurry and play a positive role in the later strength development. While meeting the slurry performance required for mine filling, it can achieve effective utilization of mine solid waste.

[0105] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0106] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A low seepage self-strengthening solid waste filling material for mining, characterized in that: The raw material components include, by weight: 340-480 parts of weathered coal gangue, 20-25 parts of cement, 30-40 parts of fly ash, 30-40 parts of slag powder, 0.3-0.7 parts of sodium silicate, 5-7 parts of quicklime, 3-5 parts of magnesium oxide, 0.05-0.1 parts of water-absorbing resin, 0.2-0.4 parts of fiber and 160-245 parts of water.

2. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The weathered coal gangue has a SiO2 content of 55-60wt%, an Al2O3 content of 20-25wt%, a Fe2O3 content of 5-9wt%, and a SO3 content of 3-6wt%.

3. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The SiO2 content in the fly ash is 40-45wt%, and the Al2O3 content is 36-42wt%; the CaO content in the slag powder is 38.0-42.0wt%, the SiO2 content is 27.0-32.0wt%, the Al2O3 content is 15.0-18.0wt%, and the MgO content is 5.0-10wt%; the CaO content in the quicklime is greater than 90.0wt%.

4. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The water-absorbing resin is selected from one or more of polyacrylic acid-based high molecular water-absorbing resin, cellulose-based high water-absorbing resin and polyacrylamide-based high water-absorbing resin.

5. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The fiber is selected from one of polypropylene fiber and basalt fiber, and the fiber has a diameter of 15 to 35 μm and a length of 6 to 20 mm.

6. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The particle size of the weathered coal gangue is ≤20 mm; the particle size of the water-absorbing resin is 10-20 μm.

7. The low water seepage self-strengthening solid waste filling material for mining according to claim 1, characterized in that: The low-bleeding self-strengthening solid waste filling material for mining has a slump of 24-27 cm, a water seepage rate of <1%, a 3-day compressive strength of 1-2 MPa, a 28-day compressive strength of 3-6 MPa, and a drying shrinkage of -20-0 mm / m.

8. A method for preparing a low-bleeding self-strengthening solid waste filling material for mining, characterized in that: The following steps are involved: Step 1, screening the weathered coal gangue, using the weathered coal gangue with a particle size greater than 150 μm as coal gangue aggregate, and using the weathered coal gangue with a particle size less than 150 μm as coal gangue powder; Step 2, activating the coal gangue powder to obtain activated coal gangue powder; Step 3: Take the formulated amount of coal gangue aggregate, activated coal gangue powder, fly ash and slag powder and mix them evenly to obtain filling dry material A; Step 4, taking the formulated amount of cement, quicklime, water-absorbing resin, magnesium oxide and fiber, mixing and stirring evenly to obtain filling dry material B; Step 5, mixing the formulated amount of sodium silicate and water to obtain a sodium silicate aqueous solution; Step 6, mixing the filling dry material A, the filling dry material B and the sodium silicate aqueous solution to obtain; Among them, the low-seepage self-reinforcing solid waste filling material for mining includes the following raw material components in parts by weight: 340-480 parts of weathered coal gangue, 20-25 parts of cement, 30-40 parts of fly ash, 30-40 parts of slag powder, 0.3-0.7 parts of sodium silicate, 5-7 parts of quicklime, 3-5 parts of magnesium oxide, 0.05-0.1 parts of water-absorbing resin, 0.2-0.4 parts of fiber and 160-245 parts of water.

9. The use of the low water seepage self-reinforcing solid waste filling material for mining as described in any one of claims 1 to 7 for filling mining; or the use of the low water seepage self-reinforcing solid waste filling material for mining obtained by the preparation method of the low water seepage self-reinforcing solid waste filling material for mining as described in claim 8 for filling mining.

Citation Information

Patent Citations

  • Coal gangue-based composite geopolymer grouting filling material and preparation method thereof

    CN111018423A

  • Fully-graded coal gangue filling paste for ultra-far pumping and preparation method of fully-graded coal gangue filling paste

    CN115028411A

  • Paste filling material and preparation method thereof

    CN115385636A

  • Fiber-reinforced alkali slag cemented coal gangue material as well as preparation method and application thereof

    CN118290079A

Cited By

  • Fiber-reinforced cement-based foam filling material and preparation method thereof

    CN120247498A